Studies on West African Dwarf sheep. The influence of age of ewe and parturition interval on neonatal lamb mortality rate - Otesile, E.B. (1993)
The influence of age and parturition interval of West African Dwarf (WAD) ewes on birth weight, serum immunoglobin (Ig) concentration and mortality rates in the neonatal lambs were examined. Age of ewe significantly influenced birth weight of lambs with effect being more pronounced on twin lambs (P